Successful conservation translocation: Population dynamics of tiger recovery in Panna Tiger Reserve, Central India - Supratim Dutta; Ramesh Krishnamurthy (Ecological Solutions and Evidence, 2024)
Abstract Tiger (Panthera tigris) is an indicator species of ecological health and conservation efforts. Due to poaching and other causes, the tiger became locally extinct in Panna Tiger Reserve, Central India. Subsequent reintroduction efforts have brought the species back from the extinction and have demonstrated the success of conservation translocations in response to such critical situations. We studied the demographic characteristics of the reintroduced tiger population based on an ensemble approach of different sampling techniques and direct observations from a long‐term dataset spanning more than 10 years. We evaluated different demographic indicators (population status, growth rate, mean litter size, inter‐birth interval and survival probability). Since reintroduction in 2009 and until the reporting period, 18 females have recruited 120 cubs from 45 litters. This led to 59 individuals in 2021 with a growth rate of ~26%. The mean litter size was 2.66 (SE 0.1), and the inter‐birth interval was 19.16 months (SE 0.5). The high survival rate of the reintroduced population (0.82 ± 0.2) helped to achieve the success of reintroduction. We observed non‐constant mortality trajectories for both sexes (higher survival probabilities for females) with a moderately higher risk of death in younger (<1 year) and older (>10 years) individuals. Our results showed the effectiveness of translocation and conservation efforts. The recovered population can be used as a founder for augmentation in other recovering tiger populations. A long‐term tiger‐centric management plan should be implemented in the area adjacent to Panna Tiger Reserve to conserve and secure the habitat of the entire landscape for the long‐term survival of the reintroduced population in a metapopulation framework.